A multi-model simulation framework for the 'Sponge Park' concept: achieving urban water-energy nexus sustainability in hyper-arid climates - Firas Fayssal (Journal of Emerging Science and Engineering, 2026)
Urban areas in hyper-arid regions face a dual threat of water scarcity and urban heat islands, exacerbated by conventional infrastructure. This study introduces and evaluates the "Sponge Park" concept—a decentralized, nature-based system of permeable surfaces and subsurface storage—as a replicable model for integrated water management and climate adaptation in arid cities. A novel multi-model computational framework was developed, coupling Computational Fluid Dynamics (CFD) for process-level subsurface hydrology and heat transfer, the EPA HELP model for long-term water balance, and TR-55/HydroCAD for extreme storm event routing. The system, designed for a 13-ha site in Abu Dhabi, integrates high-infiltration silica-sand pavers and breathable aquicludes (APAC). A comprehensive Monte Carlo analysis (n=1,000) quantified uncertainties in key parameters. Simulations under local climatic inputs (80 mm/yr rainfall) project exceptional performance: >93.6 ± 3.8% annual rainfall infiltration, <0.1% runoff for 50 mm/24h storms, and pollutant removal efficiencies of 98.0 ± 2.1% (SS) and 93.9 ± 4.2% (COD). The system harvests 5,240 ± 520 m³/yr of water for reuse. The latent heat flux from evaporation (9.32 ± 0.93 GJ/yr per 1,000 m²) translates to a microclimate cooling of 0.4–0.6 °C. A life-cycle cost analysis confirms economic viability with a net present value of +$0.42 million. The Sponge Park provides a quantitative, policy-ready blueprint for transforming arid cities. It demonstrates a sustainable pathway to achieving water security and climate resilience, directly supporting the UAE's Estidama framework, Net-Zero 2050 goal, and relevant UN Sustainable Development Goals (SDGs). The simulation-based proof-of-concept establishes a new benchmark for sponge city applications in water-stressed regions, with a defined plan for field validation.